Glandular Pseudoneoplasms of the Uterine Cervix. Issue 2 (March 2018) - Harrison, Beth T.; Nucci, Marisa R.
Abstract: Several benign glandular lesions of the uterine cervix can mimic malignancy. These glandular pseudoneoplasms include microglandular hyperplasia, lobular and diffuse laminar types of endocervical glandular hyperplasia, tunnel clusters, adenomyoma of endocervical type, mesonephric hyperplasia, ectopic prostate, endometriosis and tuboendometrioid metaplasia, and the Arias-Stella reaction, among others. Each of these entities may show a variety of unusual morphologic features that complicate the diagnosis. This review covers the clinical and pathologic features of this selected group of glandular pseudoneoplasms, as well as the immunohistochemical and molecular markers that distinguish them from premalignant and malignant lesions in the differential diagnosis. New developments in the molecular characterization of the latter are briefly discussed in regard to their potential utility in the diagnosis of selected challenging cases. For example, recurrent KRAS mutations distinguish microglandular-like endometrial adenocarcinoma from microglandular hyperplasia, as well as mesonephric and mesonephric-like carcinomas from mesonephric hyperplasia; a p53 mutant phenotype favors minimal deviation or gastric-type adenocarcinoma over lobular endocervical glandular hyperplasia (typical), tunnel clusters, endocervical adenomyomas, and other lesions, and p16 positivity has emerged as a very useful marker of human papillomavirus–related neoplasia in the appropriate clinicopathologic setting.